The prophet shuayb and the earthquake - Khan, Saniyasnain; Gurmeet (Goodword Books New Delhi, 2005)
"The Prophet Shuayb and the Earthquake" is a captivating tale that narrates the story of Prophet Shuayb (Jethro) and his mission to guide the people of Midian. Known for his wisdom and integrity, Shuayb calls upon his community to abandon their dishonest practices and to worship Allah alone. Despite his efforts, the people reject his message, leading to dire consequences. The narrative climaxes with a powerful earthquake, serving as a divine warning and punishment for their disobedience. This story emphasizes themes of faith, accountability, and the importance of heeding divine guidance, while illustrating the consequences of wrongdoing and the mercy of Allah.